Research progress in endogenous H2S‐activatable nanoplatforms for cancer theranostics. Issue 2 (1st May 2020) - Feng, Lili; Zhao, Yanli
Abstract: Hydrogen sulfide (H2 S) is a critical signaling molecule that exists in a wide variety of organizational categories, which has significant influences on several physiological functions containing vasodilatory modulation and neurotransmitter regulation. Dysregulated production and abnormal contents of H2 S are considered to be the characteristics of different types of disease occurrence; the detection and real‐time monitoring of endogenous H2 S in tissues and living cells is of great significance. However, most conventional H2 S detection methods still suffer from some inevitable drawbacks including low bioavailability, accuracy, and sensitivity, making them difficult to apply in visualizing endogenous H2 S in vivo. Optical probes constructed with the features of fast responsive time, excellent selectivity and sensitivity, as well as noninvasive performance, providing the possibility of detecting and monitoring H2 S in real‐time at the cellular and mouse levels. Such methods show the application prospect, which could avoid the defects of conventional detection approaches. Furthermore, a certain concentration of H2 S can influence the therapeutic efficacy, for example, anti‐inflammation and protection against oxidative stress, during the treatment of cancer and neurodegenerative diseases. Because the generation of overexpressed exogenous H2 S is closely tied to the tumor formation, the development of H2 S‐responsive theranostic nanoplatforms is highly needed for H2 S‐related tumor diagnosis and treatment. The theranostic nanoplatforms are expected to maximize therapeutic effectiveness and minimize side effects to normal tissues. In this review article, the current research progress, challenges, and future possibilities of H2 S‐activatable nanoplatforms for H2 S detection and malignant tumor theranostics are summarized. Abstract : Hydrogen sulfide (H2 S) is an important signaling molecule that exists in a wide variety of organizational categories, showing significant influences on several physiological functions. This review discusses current research progress, challenges, and prospects of H2 S‐activatable nanoplatforms for malignant tumor theranostics.